COVID-19 and economic recovery in compliance with climate targets - Mark Diesendorf (Global Sustainability, 2020)
A small benefit of the disastrous COVID-19 pandemic has been the temporary reduction in greenhouse gas emissions. Therefore, this paper asks: what strategies can return people to work without returning to the old high-emissions economy? How can we modify the old economic system to reduce environmental impacts while rebuilding employment? Technological change, such as replacing fossil fuels with renewable energy (RE), is necessary but, in an economy that's growing, unlikely to be sufficiently rapid to avoid dangerous climate change. Degrowth in physical consumption, especially by the ‘rich’ 10%, towards a steady-state economy, is needed as well as low-carbon jobs.